2005
DOI: 10.1002/adma.200501355
|View full text |Cite
|
Sign up to set email alerts
|

Laser Emission from a Polymer‐Stabilized Liquid‐Crystalline Blue Phase

Abstract: The possibility of controlling light emission and propagation by exploiting periodic structures of dielectric media has attracted interest in the last decade. These photonic-bandgap materials, so-called photonic crystals, have generated considerable interest due to their wide applicability in optoelectronic and microwave devices.[1] In particular, emission control and lasing action in optically active photonic crystals can offer new applications for low-threshold lasers from small-size devices. [2][3][4] Curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
140
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(145 citation statements)
references
References 18 publications
3
140
0
1
Order By: Relevance
“…[30]. Later on, the same has been reported for the phase of the type BPI [31,32]. The pumping intensity threshold is almost twice as lower than that for the ChLC samples with the same dye concentration and under the same pumping conditions.…”
Section: Lasing In Liquid Crystalssupporting
confidence: 67%
“…[30]. Later on, the same has been reported for the phase of the type BPI [31,32]. The pumping intensity threshold is almost twice as lower than that for the ChLC samples with the same dye concentration and under the same pumping conditions.…”
Section: Lasing In Liquid Crystalssupporting
confidence: 67%
“…In the bulk, however, BPs are only found in a narrow range of temperature, between the cholesteric and the isotropic phases (1-6, 10-18), thereby placing limits on their practical utility. Recent efforts have therefore focused on increasing their stability over wider ranges of temperature and chirality, for example through addition of nanoparticles (19, 20, 21-23), polymers (24-26), or by manipulating their flexoelectricity (14).Confined chiral liquid crystals are of interest for applications in optical devices (27)(28)(29)(30)(31). Simulations of chiral LCs in channels have shown that their defect structure can be manipulated through confinement, thereby raising intriguing prospects for technology (32)(33)(34)(35).…”
mentioning
confidence: 99%
“…In previous studies, optically excited laser action are successfully demonstrated by using low molecular weight bluephase LCs, 41 as well as polymer stabilized blue-phase LCs. 42 The typical experimental results of optically excited laser action from the CLCs doped with a fluorescent dye are described below (Figure 4). 43 In order to prepare the CLC hosts with PBGs in a visible wavelength range, we use two kinds of compounds of RDP-60774 as an achiral nematic LC and R-1011 as a chiral dopant (Figure 4a).…”
Section: Laser Action From Dye-doped Clcsmentioning
confidence: 99%